Polishing pad and polishing device
By using the structure of a resin molded body in the polishing pad, combining a highly hydrophilic polishing layer and a highly hydrophobic sealing layer, the problem of the polishing pad being difficult to evenly contact a large workpiece is solved, and the surface roughness of the workpiece is effectively reduced.
Patent Information
- Application Number
- CN202411139775.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-09
- Filing Date
- 2024-08-20
- Publication Date
- 2025-02-25
AI Technical Summary
In polishing processing, it is difficult for the polishing pad to evenly contact large workpieces, resulting in difficult to uniformize the surface of the workpiece and the surface roughness cannot be fully reduced.
A polishing pad formed of a resin molded body is used, and its structure includes a polishing layer and a sealing layer. The polishing layer has a higher hydrophilicity, while the sealing layer has a water contact angle of more than 90° to ensure that the fluid does not easily reach the polishing surface.
With this structure, the polishing pad can effectively follow the shape of the workpiece, avoid uneven contact, and significantly reduce the roughness of the workpiece surface.
Smart Images

Figure CN119501777A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to polishing pads and polishing apparatus. Background Art
[0002] The polishing pad is bonded to a base and is used for a polishing process to be performed in a finishing process of a semiconductor substrate and an optical lens. In the polishing process, it is necessary to perform a finishing process to make the entire surface of the workpiece to be processed uniform to eliminate uneven thickness. Semiconductor substrates and optical lenses have various sizes, ranging from a few millimeters (mm) to a few meters (m). In the finishing process for a large workpiece to be processed, a part of the polishing pad contacts unevenly due to warping of the workpiece, making it difficult to make the entire surface of the workpiece uniform. Therefore, it is necessary to improve the followability of the polishing pad to each workpiece shape and prevent the occurrence of uneven contact, so as to make the entire surface of the workpiece uniform in the finishing process. As a technology that effectively improves the followability, the stacked polishing pad discussed in Japanese Patent Application Laid-Open No. 2003-220550 and the fluid-supported polishing discussed in Japanese Patent Application Laid-Open No. 2004-358591 are known.
[0003] A laminated polishing pad refers to a pad including layers having different hardness and different elastic modulus in the thickness direction in a single pad. The upper layer of the laminated polishing pad is a hard layer having high hardness for holding the slurry on the polishing surface. The lower layer of the laminated polishing pad is a soft layer having low hardness to follow the warpage of the workpiece. In such a laminated polishing pad, it is not necessary to bond the layers with an adhesive, which is conducive to preventing the deterioration of the followability due to uneven thickness of the adhesive.
[0004] Fluid-supported polishing is a processing method in which the support surface of the polishing pad is supported by fluid. The fluid is filled at a predetermined pressure according to the warpage of the workpiece, thereby improving the followability. Summary of the invention
[0005] According to one aspect of the present disclosure, the polishing pad includes a polishing layer and a sealing layer, the polishing layer includes a polishing surface, and the sealing layer includes a supporting surface, wherein the polishing layer and the sealing layer are arranged in sequence, wherein the polishing surface is set as the front side, and the supporting surface is set as the back side, wherein the supporting surface has a water contact angle of more than 90°, wherein the water contact angle of the polishing surface is smaller than the water contact angle of the supporting surface, and wherein the polishing pad is formed of a resin molded body.
[0006] Further features of the present disclosure will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 is a schematic diagram of a polishing apparatus.
[0008] Figure 2Ais a schematic stereogram of a polishing pad, Figure 2B is along Figure 2A Schematic cross-sectional view of the polishing pad taken along line AA, Figure 2C is along Figure 2A Schematic cross-sectional view of the polishing pad taken along line AA.
[0009] Figure 3 is a flow chart showing the polishing pad manufacturing process.
[0010] 4A to 4D Schematic diagrams respectively showing the polishing pad manufacturing steps.
[0011] Figure 5A is a schematic stereogram of a polishing pad, Figure 5B is along Figure 5A Schematic cross-sectional view of the polishing pad taken along line AA.
[0012] Figure 6 is a flow chart showing the polishing pad manufacturing process.
[0013] FIG. 7A to FIG. 7D The following are schematic diagrams showing the steps of manufacturing a polishing pad. DETAILED DESCRIPTION
[0014] [Polishing device]
[0015] Figure 1 Schematic diagram of a polishing device according to the present disclosure. The polishing device 1 includes: a polishing pad 10; a base 5 for fixing the polishing pad 10; a fluid storage portion 6 for storing a fluid that applies pressure from the lower surface side (sealing layer side) of the polishing pad 10; and a supply portion 2 for supplying a slurry S (e.g., water or a polishing solution) to the polishing surface of the polishing pad 10. The polishing device 1 is a wet polishing processing device, which is a type of device in which the polishing pad is supported by a fluid.
[0016] The fluid storage portion 6 is used to store a liquid or a gas as a fluid supplied from the sealing layer side of the polishing pad 10 to the supporting surface of the polishing pad 10 at a predetermined pressure. The type of fluid is not particularly limited. Examples of fluids in gas form include air, compressed air, and nitrogen. Examples of fluids in liquid form include pure water and polishing solutions. The magnitude of the pressure to be applied to the polishing pad 10 can be approximately the pressure that the polishing pad 10 can support, and is not particularly limited. For example, the pressure is in the range of 3 kPa to 40 kPa. The pressure is preferably in the range of 5 kPa to 20 kPa.
[0017] like Figure 1As shown, the workpiece carrier 4 applies force to the workpiece 3 from the upper surface of the workpiece 3 to be processed, so that the workpiece 3 contacts the polishing surface of the polishing pad 10. The workpiece 3 is, for example, a semiconductor substrate or an optical lens. The object obtained by polishing the workpiece 3 is defined as an article in this article.
[0018] [Polishing pad]
[0019] FIG. 2A to FIG. 2C 1 and 2 are schematic diagrams respectively showing a polishing pad 10 according to the present disclosure. Figure 2A is a perspective view of the polishing pad 10, Figure 2B is along Figure 2A The cross-sectional view of the polishing pad 10 is taken along line AA in the z-axis direction.
[0020] exist FIG. 2A to FIG. 2C In FIG. 1 , a plane parallel to the polishing surface 11S is defined as an xy plane, and an axis perpendicular to the xy plane is defined as a z axis. Figure 2A The line AA shown by the middle dashed line is parallel to the x-axis and perpendicular to the y-axis. In the polishing pad 10, the polishing layer 11, the intermediate layer 12, and the sealing layer 13 are sequentially positioned (arranged sequentially) from the polishing surface 11S in the negative z-direction. The polishing pad 10 according to the present disclosure is a polishing pad obtained by sequentially arranging the polishing layer 11 and the sealing layer 13. The polishing pad 10 includes a polishing surface 11S formed on the front side of the polishing pad 10 and having higher hydrophilicity than the supporting surface 13S, and also includes a supporting surface 13S formed on the back side of the polishing pad 10 and having hydrophobicity (indicated by a water contact angle of 90° or more).
[0021] The polishing layer 11 includes a polishing surface 11S. The polishing surface 11S is a portion of the polishing pad 10 that contacts the workpiece 3, and includes a resin 7. The water contact angle of the polishing surface 11S is smaller than the water contact angle of the supporting surface 13S. The polishing surface 11S has a higher wettability than the supporting surface 13S. Therefore, the slurry S is easy to wet on the polishing surface 11S. If the slurry S is easy to wet on the polishing surface 11S, the surface roughness of the workpiece 3 can be reduced compared to the case where the slurry S is not fully wetted on the polishing surface 11S. The water contact angle of the polishing surface 11S is preferably less than 90°. More preferably, the water contact angle of the polishing surface 11S is less than 75°, and more preferably less than 25°.
[0022] The cells 8 are preferably located in the polishing surface 11S. The cells 8 located in the polishing surface 11S enable the polishing surface 11S to hold the slurry S on the front surface. If the polishing surface 11S can hold the slurry S, the slurry S can be supplied to the space between the polishing pad 10 and the workpiece 3 even if the polishing pad 10 and the workpiece 3 are in contact with each other during the polishing process. The polishing layer 11 has a predetermined hardness and is used to prevent the polishing pad 10 from following the shape of a portion of the workpiece 3 to be removed by polishing (e.g., a corrugated portion with a high spatial frequency). By controlling the amount of cells 8 (average cell density), the desired hardness of the polishing layer 11 can be obtained. For example, the cavity portion of a hollow particle can be used as the cell 8, and if the amount of the cell 8 is increased by increasing the hollow particle content, the hardness of the polishing layer 11 can be reduced; if the amount of the cell 8 is reduced by reducing the hollow particle content, the hardness of the polishing layer 11 can be increased. Hardness refers to the indentation hardness represented by Pa. The average cell density in the polishing layer 11 is not particularly limited, and is, for example, in the range of 40% to 80%.
[0023] The polishing layer 11 preferably contains metal oxide particles 24 having hydrophilicity in the resin 7. Having hydrophilicity means that the hydrophilization rate is greater than or equal to 0.50. Metal oxide particles having hydrophilicity mean that the hydrophilization rate of the particle surface is greater than or equal to 0.50. The method for measuring the hydrophilization rate will be described later. Particles having hydrophilicity on the surface have greater free energy. Therefore, if the polishing layer 11 contains metal oxide particles 24, the polishing surface 11S is easier to retain the polishing solution or slurry. In other words, if the polishing layer 11 contains metal oxide particles 24 having hydrophilicity, the roughness on the polishing surface of the workpiece 3 is easy to reduce. The type of metal oxide is not particularly limited. From the viewpoint of large surface free energy, silicon dioxide and aluminum oxide are preferably used. Silica and aluminum oxide can be used separately or in combination. If the content of the metal oxide particles 24 in the polishing layer 11 is less than 20% by mass, the water contact angle increases, which makes it difficult to obtain sufficient polishing characteristics. On the other hand, if the content of metal oxide particles 24 exceeds 50 mass %, the hardness of polishing layer 11 increases, which makes it difficult to obtain sufficient followability. Therefore, the content of metal oxide particles 24 in polishing layer 11 is preferably in the range of 20 mass % to 50 mass %.
[0024] The intermediate layer 12 is a portion located between the polishing layer 11 and the sealing layer 13, and includes a resin 7. In the polishing pad 10 according to the present disclosure, the intermediate layer 12 may be omitted. The intermediate layer 12 may include cells 8 and metal oxide particles 24 in the resin 7 like the polishing layer 11. The intermediate layer 12 may include cells 8 and fluororesin particles 9 in the resin 7 like the sealing layer 13 to be described below. From the viewpoint of facilitating the polishing pad 10 to follow the shape of the workpiece 3, the hardness of the intermediate layer 12 is preferably lower than that of the polishing layer 11. Therefore, the average cell density in the intermediate layer 12 is preferably lower than that in the polishing layer 11.
[0025] The sealing layer 13 includes a support surface 13S of the polishing pad 10. The support surface 13S is located on the opposite side of the polishing surface 11S in the polishing pad 10. The support surface 13S is a surface to which the fluid is applied from the fluid storage portion 6 at a predetermined pressure in the fluid-supported polishing, and is supported by the fluid during the polishing operation. When the support surface 13S is supported by the liquid, the support surface 13S also includes a function for preventing the liquid from infiltrating the polishing surface 11S.
[0026] The water contact angle of the support surface 13S is 90° or more. The water contact angle of the support surface 13S is greater than the water contact angle of the polishing surface 11S. In this way, a structure for preventing a fluid in liquid form from entering the polishing pad 10 can be provided. In other words, the support surface 13S has a higher hydrophobicity than the polishing surface 11S. The water contact angle of the support surface 13S is preferably in the range of 90° to 150°. In order to obtain a water contact angle greater than 150°, the support surface 13S may preferably contain a large amount of fluororesin particles 9 described below, which will result in an increase in hardness.
[0027] The sealing layer 13 includes a resin 7 and cells 8. The average cell density in the sealing layer 13 is not particularly limited, for example, in the range of 40% to 80%. If the average cell density in the sealing layer 13 is too high, the cells 8 are easily connected to each other. In this case, the fluid supplied from the fluid storage portion 6 reaches the workpiece 3 via the support surface 13S, the sealing layer 13, the intermediate layer 12, the polishing layer 11, and the polishing surface 11S. The thickness of the sealing layer 13 ( Figure 2B The length in the z-direction) is preferably smaller than the thickness of the polishing layer 11 and the thickness of the intermediate layer 12.
[0028] From the viewpoint of improving the hydrophobicity of the sealing layer 13, the sealing layer 13 preferably contains fluororesin particles 9. As the type of fluororesin particles used, for example, at least one type selected from the group consisting of polytetrafluoroethylene (PTFE = tetrafluoroethylene), tetrafluoroethylene-perfluoroalkoxyethylene copolymer resin (PFA), tetrafluoroethylene-hexafluoropropylene copolymer resin (FEP), tetrafluoroethylene-hexafluoropropylene-perfluoroalkoxyethylene copolymer resin (EPE), tetrafluoroethylene-ethylene copolymer resin (ETFE), polytrifluorochloroethylene resin (PCTFE), ethylene-trifluorochloroethylene copolymer resin (ECTFE), polyvinylidene fluoride resin (PVDF), and fluoroethylene resin (PVE) can be used. In this group, polytetrafluoroethylene (PTFE) is preferably used. PTFE is a substance excellent in heat resistance and chemical resistance, and has a small surface free energy of 18.5mN / m. PTFE is effective in increasing the hydrophobicity of the sealing layer 13 and enhancing the function of preventing liquid from infiltrating the polishing surface 11S. The content of fluororesin particles 9 in sealing layer 13 is preferably in the range of 20% to 50% by mass. The content of fluororesin particles 9 in this range allows the water contact angle and hardness to be well balanced, so that sufficient followability can be obtained.
[0029] like Figure 2C As shown, the pores 8 preferably have a flattened shape in the stacking direction. This is because a higher followability to the shape or warping of the workpiece 3 can be maintained. In particular, the pores 8 preferably have a flattened shape in the stacking direction in all layers. In the polishing pad 10 according to the present disclosure, the pores 8 have different diameters. Therefore, the diameter of the largest pore 8 preferably exceeds the thickness of each layer. If the pores 8 do not have a flattened shape in the stacking direction, the pores 8 in all layers are easily connected to each other. In this case, the fluid supplied from the fluid storage portion 6 is likely to reach the workpiece 3 via the support surface 13S, the sealing layer 13, the intermediate layer 12, the polishing layer 11 and the polishing surface 11S. Therefore, the thickness of the flattened shape is preferably less than or equal to the thickness of each layer. The diameter (average pore diameter) of the pores 8 in the polishing surface 11S is preferably in the range of 50μm to 300μm. If the diameter is less than 50μm, it will be difficult to maintain the slurry and difficult to supply a sufficient amount of slurry S to the polishing pad 10 and the workpiece 3 under certain manufacturing conditions. If the diameter is larger than 300 μm, uneven pressure is applied to the surface of the workpiece 3 , which may result in increased surface roughness.
[0030] The polishing pad 10 is a resin molded body. Specifically, the polishing surface 11S, the polishing layer 11, the intermediate layer 12, the sealing layer 13 and the supporting surface 13S are integrally formed without using an adhesive. The resin molded body is preferably a foamed body. In this case, the polishing surface 11S has a concavoconvex shape. The raw material of the resin material used as the curing material for forming the resin molded body is not particularly limited. For example, polyurethane, polyethylene, polypropylene, polystyrene, polyester, nylon, polyvinyl chloride, polyvinylidene chloride, polybutene, polyacetal, polyphenylene ether, polyvinyl alcohol, polymethyl methacrylate, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyamideimide, polycarbonate, polyarylate, liquid crystal polymer, aromatic polysulfone resin, biodegradable polyester resin, polyamide resin, polyimide resin, fluororesin, ethylene-propylene resin, ethylene-ethyl acrylate resin, epoxy resin, acrylic resin, norbornene-based resin, styrene copolymers (e.g., vinyl polyisoprene-styrene copolymers, butadiene-styrene copolymers, acrylonitrile-styrene copolymers, or acrylonitrile-butadiene-styrene copolymers), natural rubber, synthetic rubber, or thermoplastic elastomer can be used.
[0031] Examples of these resin materials may be used alone, or may be mixed or copolymerized. From the viewpoint of excellent wear resistance or from the viewpoint of convenience of the manufacturing process described below, it is preferred to use polyurethane as the main component. The term "main component of a resin molded body" as used herein refers to the component with the largest mass among the resin materials contained in the resin molded body when the resin molded body is formed from a plurality of resin materials. The proportion of polyurethane in the resin molded body is greater than or equal to 50% by mass, preferably greater than or equal to 70% by mass, and more preferably greater than or equal to 90% by mass. The method for manufacturing the resin molded body will be described later.
[0032] The water vapor permeability of the polishing pad 10 is preferably 25 g / m 2 · 24hr or less. If the water vapor permeability is less than or equal to this value, the fluid supplied from the fluid storage portion 6 to the supporting surface 13S of the polishing pad 10 does not easily reach the polishing surface 11S, which helps the polishing pad 10 to follow the shape of the workpiece 3. On the other hand, if the water vapor permeability is greater than this value, the fluid easily reaches the polishing layer 11. Fluid leakage makes it difficult for the polishing pad 10 to follow the shape of the workpiece 3. If it is difficult for the polishing pad 10 to follow the shape of the workpiece 3, the polishing process cannot be fully performed, which makes it difficult to reduce the surface roughness of the workpiece 3. More preferably, the water vapor permeability is 13g / m 2 Less than 24 hours.
[0033] The thickness of the polishing pad 10 ( Figure 2BThe length in the z direction in the middle) is preferably in the range of 0.3 mm to 2.0 mm. This is because: if the thickness of the polishing pad 10 is within this range, the polishing pad 10 is easy to follow the shape or warping of the workpiece 3. The thickness of the polishing layer 11 is reduced due to the wear of the front side of the polishing pad 10 during the polishing process. Therefore, from the perspective of cost, the thickness of the polishing layer 11 is preferably 1.0 mm or more. In addition, it is preferred to use a sealing layer 13 with a smaller thickness to increase the area of the region used for polishing. Therefore, the sealing layer 13 is preferably 0.5 mm or less.
[0034] The polishing pad 10 according to the present disclosure is formed of a resin molded body having the following structure, wherein a polishing layer 11 and a sealing layer 13 are sequentially stacked, the polishing layer 11 includes a polishing surface 11S having a water contact angle smaller than that of a supporting surface 13S, and the sealing layer 13 includes a supporting surface 13S having a water contact angle of 90° or more. This structure makes it possible to prevent the fluid from reaching the polishing surface 11S even when the polishing pad 10 is used for fluid-supported polishing and fluid pressure is applied. In addition, since the polishing pad 10 is formed of a resin molded body and does not include any adhesive layer made of an adhesive, a higher tracking property to the shape or warping of the workpiece 3 can be maintained. Therefore, compared with the polishing pad for fluid-supported polishing according to the prior art, the polishing pad 10 according to the present disclosure can sufficiently reduce the surface roughness of the workpiece 3.
[0035] [Manufacturing method of polishing pad]
[0036] Next, a method for manufacturing the polishing pad 10 will be described. The method for manufacturing the polishing pad 10 according to the present disclosure is not particularly limited. Figure 3 and 4A to 4D Describe the preferred method.
[0037] First, in step S1, Figure 4AAs shown, the sealing layer precursor is placed in the mold 20, and then the sealing layer precursor is heated to temporarily cure it. The sealing layer precursor 13A is a mixture of a thermoplastic resin, a curing agent and the first hollow particles. The sealing layer precursor 13A becomes the sealing layer 13 of the polishing pad 10 after formal curing. The front of the sealing layer 13 corresponds to the support surface 13S. The size and type of the mold 20 are not particularly limited. The mold 20 can be formed into a desired size according to the shape of the polishing pad 10 to be manufactured. The mold 20 is, for example, a mold. The upper surface of the mold 20 or the opposite side surfaces of the mold 20 can preferably be movable, and the mold 20 can preferably be provided with a discharge hole that can be opened and closed to discharge excess resin when performing mold closing. In the case of mixing the thermoplastic resin, the curing agent and the first hollow particles, it is preferred to use a degasser or the like to remove bubbles. The temporary curing temperature can be less than or equal to the formal curing temperature described below, and can be appropriately set according to the material of the thermoplastic resin used. If the temporary curing temperature is equal to the formal curing temperature, the temporary curing time is preferably shorter than the formal curing time.
[0038] Next, in step S2, Figure 4B As shown, the intermediate layer precursor is placed on the temporarily cured sealing layer precursor 13A in the mold 20, and then the intermediate layer precursor is heated to temporarily cure it. The intermediate layer precursor 12A is a mixture of a thermoplastic resin, a curing agent and the third hollow particles. The intermediate layer precursor 12A becomes the intermediate layer 12 of the polishing pad 10 after formal curing. In the case of mixing thermoplastic resin, curing agent and the third hollow particles, it is preferred to use a degasser or the like to remove bubbles. The temporary curing temperature is preferably less than or equal to the formal curing temperature described below, and can be appropriately set according to the material of the thermoplastic resin used. If the hardness of the intermediate layer 12 is higher than the hardness of the sealing layer 13, the content and / or particle size of the third hollow particles are selected so that the cell density in the intermediate layer 12 is lower than the cell density in the sealing layer 13. In this case, the average particle size of the third hollow particles is preferably smaller than the average particle size of the first hollow particles. The linear expansion coefficient of the third hollow particles is preferably smaller than the linear expansion coefficient of the first hollow particles. If the hardness of the intermediate layer 12 is lower than the hardness of the sealing layer 13, the content and / or particle size of the third hollow particles are selected so that the cell density in the intermediate layer 12 is higher than the cell density in the sealing layer 13. In this case, the average particle size of the third hollow particles is preferably greater than the average particle size of the first hollow particles. The linear expansion coefficient of the third hollow particles is preferably greater than the linear expansion coefficient of the first hollow particles.
[0039] Next, in step S3, Figure 4CAs shown, the polishing layer precursor is placed on the temporarily cured intermediate layer precursor 12A in the mold 20, and then the polishing layer precursor is heated to be temporarily cured. The polishing layer precursor 11A is a mixture of a thermoplastic resin, a curing agent, and a second hollow particle. The polishing layer precursor 11A becomes the polishing layer 11 of the polishing pad 10 after formal curing. In the case of mixing the thermoplastic resin, the curing agent, and the second hollow particle, it is preferred to use a degasser or the like to remove bubbles. The temporary curing temperature is preferably less than or equal to the formal curing temperature described below, and can be appropriately set according to the material of the thermoplastic resin used. If the temporary curing temperature is equal to the formal curing temperature, the temporary curing time is preferably shorter than the formal curing time.
[0040] In step S4, Figure 4D As shown, the inside of the mold 20 is compressed while the sealing layer precursor 13A, the intermediate layer precursor 12A and the polishing layer precursor 11A are heated for formal curing, and each precursor is maintained until it no longer flows. The sealing layer precursor 13A, the intermediate layer precursor 12A and the polishing layer precursor 11A are formally cured to form the sealing layer 13, the intermediate layer 12 and the polishing layer 11. Therefore, a resin foam including flattened cells obtained by compression in a mold can be manufactured. The formal curing temperature may be greater than or equal to the above-mentioned temporary curing temperature, and may be appropriately set according to the material of the thermoplastic resin used. If the temporary curing temperature is equal to the formal curing temperature, the formal curing time is preferably longer than the temporary curing time. In the compression in the mold 20, the top cover is placed on the top of the mold 20, and the top cover is moved while curing in the formal curing process, and this state is maintained until each precursor no longer flows. The temporarily cured resin maintains fluidity under high temperature and high pressure conditions. This enables the flattened cells to be obtained. The degree of compression is preferably 50% to 95% of the initial thickness, more preferably 55% to 75% of the initial thickness. In this case, each cell has a flattened shape in the moving direction of the top cover of the mold 20. If the flattened cells are not formed, the formal curing process can be performed after the temporarily cured precursor of the polishing pad 10 is demolded from the mold 20 after step S3.
[0041] Through the above steps, the polishing pad 10 according to the present disclosure can be manufactured.
[0042] The method for manufacturing the polishing pad 10 according to the present disclosure does not include any process using an adhesive, so it is possible to provide a polishing pad that can maintain a high degree of followability to the shape or warpage of the workpiece 3. Therefore, compared with the polishing pad for fluid-supported polishing according to the prior art, the method for manufacturing the polishing pad 10 according to the present disclosure can provide a polishing pad that can minimize the surface roughness of the workpiece 3.
[0043] In the above-mentioned manufacturing method, temporary curing and formal curing are performed by placing the sealing layer precursor 13A, the intermediate layer precursor 12A, and the polishing layer precursor 11A in the mold 20 in sequence. Alternatively, temporary curing and formal curing may be performed by placing the polishing layer precursor 11A, the intermediate layer precursor 12A, and the sealing layer precursor 13A in the mold 20 in sequence. In addition, in the above-mentioned manufacturing method, the hardness of each layer is adjusted by changing the size or content of the hollow particles. The method of adjusting the hardness of each layer is not limited to this example. For example, the hardness of each layer can be controlled by intentionally foaming the precursor when mixing the precursors in each layer.
[0044] In the case of manufacturing the polishing pad 10 not including the intermediate layer 12, step S2 may be omitted. In this case, the polishing layer precursor 11A is directly placed on the temporarily cured sealing layer precursor 13A.
[0045] Examples of the present disclosure will be described in more detail below. However, the present disclosure is not limited by the following examples.
[0046] Before describing the manufacturing examples, a method for evaluating each example and each comparative example will be described.
[0047] [Evaluation method of polishing pad]
[0048] (Water contact angle)
[0049] Measuring instrument: Contact angle meter (VCA-2500XE manufactured by AST Products Inc.)
[0050] Test method: After pure water (1 μL) was dropped from a microsyringe coated with polytetrafluoroethylene (PTFE) having an inner diameter of 0.1 mm onto the polishing surface and the supporting surface of the polishing pad, the water contact angle was measured immediately.
[0051] (Hydrophilicity Percentage)
[0052] Measuring instrument: Fourier transform infrared spectrometer (FT-IR-NIRA manufactured by PerkinElmer, Inc.)
[0053] Test method: The hydrophilicity percentage of silica particles is determined by measuring the 7300 cm-1 Si-OH band in the infrared radiation (IR) spectrum of its surface. -1 The absorbance at 4500 cm is divided by the absorbance at 4500 cm representing SiO2. -1 The hydrophilicity of the alumina particles was calculated by measuring the absorbance at 3690 cm-1 representing Al-OH in the IR spectrum of the surface. -1 The absorbance at 7425 cm is divided by the absorbance at 7425 cm representing Al2O3. -1 The absorbance at is calculated.
[0054] (Water vapor permeability)
[0055] Measuring instrument: Gas permeation tester (PERMATRAN-W1 / 50 manufactured by Mocon, Inc.)
[0056] Test method: Evaluation was performed according to JIS Z 0208 water vapor permeability test method (cup method) (test conditions: temperature 40°C, humidity 90% RH).
[0057] (Average cell density)
[0058] Measuring instrument: Color 3D laser microscope (VK-9700 manufactured by Keyence Corporation)
[0059] Test method: The average cell density is calculated by measuring the cross section of a sample (10 mm × 10 mm) with a 10x objective lens, converting the resin portion and the cell portion into grayscale by image processing, and binarizing the obtained information at 125 grayscales.
[0060] (Average cell diameter)
[0061] Measuring instrument: Color 3D laser microscope (VK-9700 manufactured by Keyence Corporation)
[0062] Test method: The average cell diameter is calculated by measuring the entire surface of the polished surface of the sample (10 mm × 10 mm) by stitching using a 10x objective lens, and by totaling the cell diameters in an image obtained by converting the resin part and the cell part into grayscale through image processing and binarizing the obtained information at 125 grayscales.
[0063] (Cell thickness)
[0064] Measuring instrument: Color 3D laser microscope (VK-9700 manufactured by Keyence Corporation)
[0065] Test method: The thickness of each cell in the stacking direction is measured from the image obtained by measuring the cross section of the sample (10 mm × 10 mm) using a 10x objective lens, converting the resin part and the cell part into grayscale through image processing, and binarizing the obtained information at 125 grayscale.
[0066] (Thickness of each layer)
[0067] Measuring instrument: Color 3D laser microscope (VK-9700 manufactured by Keyence Corporation)
[0068] Test method: The thickness of each layer was also measured from the cross section of the sample (10 mm×10 mm) using a 10x objective lens.
[0069] (Workpiece roughness)
[0070] Measuring instrument: White interferometer (CP300 manufactured by Zygo, Inc.)
[0071] Test method: Use a 5x objective lens to measure the area 35mm to the left and 35mm to the right of the center of the test workpiece (φ80mm) and evaluate the roughness Rz (JIS B 0601-2001) of the entire measurement area. The resolution is 0.01nm.
[0072] (Follow-up)
[0073] Test method: Using a glass substrate workpiece with a surface roughness of 50nmRz and a diameter of φ80mm, polishing was performed for 30 minutes by adding cerium oxide (K30-9 manufactured by Mirek Corporation) as a slurry, and the maximum roughness Rz was evaluated. In this case, the maximum roughness of 1nmRz was set as the judgment value for determining whether the polishing pad can follow the shape of the workpiece. This is because: if the polishing pad cannot follow the shape of the workpiece and cannot be polished uniformly, an unprocessed portion will remain and a roughness less than or equal to the judgment value cannot be obtained. The result with a roughness less than or equal to 1nmRz is evaluated as "A", and the result with a roughness greater than 1nmRz is evaluated as "B".
[0074] (Structural components)
[0075] Measuring instrument: FE-SEM (product name: JSM-IT500HR / LA manufactured by JEOL Ltd.)
[0076] Test method: A method for measuring the content of metal oxide particles will be described. A first observation area obtained by arbitrarily selecting a square area with a side length of 1 mm (stitching measurement was performed on an image size of 260 μm×190 μm) in a range from the polished surface to a position 5 μm deep from the polished surface on a cross section in the thickness direction taken along a line parallel to the longitudinal direction of the polished layer was set. In the first observation area, an energy dispersive X-ray spectroscopy (EDS) image was obtained under the conditions of 500 times and 10 kV, and numerical calculation software (product name: MathWorks, Inc. manufactured by ) is binarized to obtain a binary image. In the obtained binary image, the ratio of the number of pixels in the area corresponding to the hydrophilic metal oxide particles to the number of pixels in the entire measurement area (resolution of 2083 lengths × 2083 widths) is calculated.
[0077] A method for measuring the fluororesin particle content will be described. A second observation area is set, which is obtained by arbitrarily selecting a square area with a side length of 50 μm (stitching measurement is performed on an image size of 260 μm×190 μm) in a range from the support surface to a position 5 μm deep from the support surface on a cross section in the thickness direction taken along a line parallel to the longitudinal direction of the sealing layer. In the second observation area, an EDS image is obtained under the conditions of 500 times and 10 kV, and the numerical calculation software (product name: MathWorks, Inc. manufactured by ) is binarized to obtain a binary image. In the obtained binary image, the ratio of the number of pixels in the area corresponding to the fluororesin particles to the number of pixels in the entire measurement area (resolution of 2083 lengths × 2083 widths) is calculated.
[0078] [Manufacture of polishing pad]
[0079] In Example 1, 28.98 g of diphenylmethane diisocyanate (MDI) type polyurethane elastomer Coronate 4370 (manufactured by TOSOH CORPORATION), that is, a thermoplastic resin, was weighed as a resin material for the sealing layer, and 20.28 g of polyol-based curing agent Nipporan 4479 (manufactured by TOSOH CORPORATION) was weighed as a curing agent, and these materials were mixed. In this mixture, 0.78 g of Matsumoto Microsphere FN-78D (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) and 3.06 g of polytetrafluoroethylene particles ALGOFLON L203R (manufactured by Solvay Corporation) were weighed as first hollow particles, and a sealing layer precursor was prepared by mixing the particles in three groups (48 seconds in total) for 16 seconds each with less heat influence using an automatic mixer (2-913-01 automatic mixer AS100 manufactured by AS ONE Corporation, with a rotation speed of 3000 rpm).
[0080] Likewise, 28.98 g of diphenylmethane diisocyanate (MDI) type polyurethane elastomer Coronate 4370 (manufactured by TOSOH CORPORATION), i.e., a thermoplastic resin, was weighed as a resin material for the polishing layer, and 20.28 g of polyol-based curing agent Nipporan 4479 (manufactured by TOSOH CORPORATION) was weighed as a curing agent, and these materials were mixed. In this mixture, 0.99 g of Matsumoto Microsphere F-80DE (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) was weighed as a third hollow particle, and the particles were mixed using an automatic mixer (2-913-01 automatic mixer AS100 manufactured by AS ONE Corporation, with a rotation speed of 3000 rpm) for 16 seconds per group and three groups (48 seconds) with less heat influence to prepare a polishing layer precursor. In a square mold having a lower surface of 200 mm×200 mm, 2.67 g of the sealing layer precursor was placed and temporarily cured at 120° C. for 10 minutes in an electric furnace. Next, 8.00 g of the polishing layer precursor was placed on the temporarily cured sealing layer precursor, and the polishing layer precursor was temporarily cured at 120° C. for 1 hour in an electric furnace. Thereafter, the temporarily cured polishing pad precursor was demolded from the mold. Then, the polishing pad precursor was secondary cured at a temperature of 120° C. for 8 hours. In this way, a polishing pad according to Example 1 was obtained.
[0081] In the polishing pad according to Example 1, the thickness of the sealing layer is 0.11 mm, and the thickness of the polishing layer is 0.21 mm. The water contact angle of the supporting surface is 90.6°, and the cell density in the sealing layer is 62%. The water contact angle of the polishing surface is 73.9°, and the cell density in the polishing layer is 61%. The water vapor permeability is 18.6 g / m 2 ·24h.
[0082] Table 1 shows a list of the water contact angle of the polishing surface, the water contact angle of the support surface, the fluororesin particle content, the water vapor permeability, the workpiece roughness, and the followability evaluation results. As can be seen from Table 1, it was confirmed that in Example 1 the roughness was less than or equal to 1 nmRz and therefore the polishing pad was able to completely follow the shape of the workpiece.
[0083] In Example 2, the amount of polytetrafluoroethylene particles added was increased to 7.5 g to increase the water contact angle of the sealing layer. In the subsequent process from degassing to curing, a polishing pad was prepared in the same manner as in Example 1. In the mold, 16.8 g of the sealing layer precursor was placed, and 42.8 g of the polishing layer precursor was placed on the temporarily cured sealing layer precursor, and then the precursor was formally cured.
[0084] In the polishing pad according to Example 2, the thickness of the sealing layer was 0.63 mm, and the thickness of the polishing layer was 1.07 mm. The water contact angle of the supporting surface was 149.5°, and the cell density in the sealing layer was 59%. The water contact angle of the polishing surface was 74.7°, and the cell density in the polishing layer was 62%. The water vapor permeability was 12.1 g / m 2 ·24h.
[0085] As can be seen from Table 1, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 2, so the polishing pad could completely follow the workpiece shape. Although the water contact angle of the sealing layer in Example 2 was greater than that in Example 1, it was confirmed that the water contact angle had little effect on the maximum roughness.
[0086] In Example 3, the precursor was prepared according to the same procedure as in Example 2. However, in Example 3, 0.47 g of hydrophilic silica having a hydrophilization ratio of 0.51 was added. 380PE (manufactured by NIPPON AEROSIL CO., LTD.) was added to the polishing layer precursor. In the subsequent process from degassing to curing, a polishing pad according to Example 3 was prepared in the same manner as in Example 1. In the mold, 12.53 g of the sealing layer precursor was placed and temporarily cured, and then 38.00 g of the polishing layer precursor was placed on the sealing layer precursor and formally cured.
[0087] In the polishing pad according to Example 3, the thickness of the sealing layer is 0.47 mm, and the thickness of the polishing layer is 0.95 mm. The water contact angle of the supporting surface is 120.8°, and the cell density in the sealing layer is 59%. The water contact angle of the polishing surface is 49.5°, and the cell density in the polishing layer is 60%. The water vapor permeability is 15.3 g / m 2 ·24h.
[0088] As shown in Table 1, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 3 and thus the polishing pad could completely follow the shape of the workpiece. Compared with Example 2, the polishing pad according to Example 3 contained hydrophilic metal oxide particles, so the polishing solution was easily retained on the polishing surface, resulting in a reduction in roughness.
[0089] In Example 4, the precursor was prepared according to the same procedure as in Example 3. In addition, in Example 4, 0.24 g of hydrophilic aluminum oxide having a hydrophilization ratio of 0.52 was added. Alu130 (manufactured by NIPPON AEROSIL CO., LTD.) was added to the polishing layer precursor. In the subsequent process from degassing to curing, a polishing pad according to Example 4 was prepared in the same manner as in Example 1. In the mold, 12.53 g of the sealing layer precursor was placed and temporarily cured, and then 38.00 g of the polishing layer precursor was placed on the sealing layer precursor and formally cured.
[0090] In the polishing pad according to Example 4, the thickness of the sealing layer is 0.47 mm, and the thickness of the polishing layer is 0.95 mm. The water contact angle of the supporting surface is 121.9°, and the cell density in the sealing layer is 59%. The water contact angle of the polishing surface is 49.8°, and the cell density in the polishing layer is 60%. The water vapor permeability is 15.3 g / m 2 ·24h.
[0091] As can be seen from Table 1, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 4, so the polishing pad could completely follow the shape of the workpiece. It was also confirmed that, compared with Example 3, even when hydrophilic alumina was used, polishing accuracy comparable to that when hydrophilic silica was used could be obtained.
[0092] In Example 5, the precursor was prepared according to the same procedure as in Example 3. In addition, in Example 5, 1.15 g of hydrophilic silica having a hydrophilization ratio of 0.51 was added. 380PE (manufactured by NIPPON AEROSIL CO., LTD.) was added to the polishing layer precursor. In the subsequent process from degassing to curing, a polishing pad according to Example 5 was prepared in the same manner as in Example 1. In the mold, 12.53 g of the sealing layer precursor was placed and temporarily cured, and then 43.60 g of the polishing layer precursor was placed on the sealing layer precursor and formally cured.
[0093] In the polishing pad according to Example 5, the thickness of the sealing layer is 0.47 mm, and the thickness of the polishing layer is 1.09 mm. The water contact angle of the supporting surface is 120.8°, and the cell density in the sealing layer is 60%. The water contact angle of the polishing surface is 49.5°, and the cell density in the polishing layer is 62%. The water vapor permeability is 14.8 g / m 2 ·24hr.
[0094] As shown in Table 1, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 5, so the polishing pad could completely follow the shape of the workpiece, and thus the polishing pad could fully follow the shape of the workpiece. Unlike Example 2, the polishing pad according to Example 5 contained hydrophilic metal oxide particles, so the polishing solution was easily retained on the polishing surface, which resulted in a reduction in roughness.
[0095] In Example 6, the precursor was prepared according to the same procedure as in Example 5. In addition, in Example 6, Matsumoto Microsphere FN-78D (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) was added to the polishing layer precursor as a third hollow particle. In order to perform the compression process, 18.98 g of the sealing layer precursor was placed in the mold and temporarily cured, and then 66.06 g of the polishing layer precursor (increased in amount) was placed on the sealing layer precursor. After that, the discharge hole with a diameter of φ3 mm formed in the side surface of the mold was opened, and the top cover was covered on the upper surface of the mold. While the precursor was heated for formal curing, the top cover was moved to compress the inside of the mold until the thickness became 66% of the initial thickness before compression. This state was maintained until the resin no longer flowed. Excess resin was discharged from the discharge hole.
[0096] In the polishing pad according to Example 6, the thickness of the sealing layer is 0.47 mm, and the thickness of the polishing layer is 1.09 mm. The maximum thickness of each cell in the sealing layer in the stacking direction is 0.42 mm, the thickness of each cell in the polishing layer in the stacking direction is 0.98 mm, and the average cell diameter in the polishing surface is 300 μm. The maximum cell diameter is 1.8 mm, and each cell has a flattened shape in the stacking direction. The water contact angle of the supporting surface is 120.6°, and the cell density in the sealing layer is 60%. The water contact angle of the polishing surface is 49.5°, and the cell density in the polishing layer is 62%. The water vapor permeability is 9.2 g / m 2 ·24h.
[0097] As can be seen from Table 1, it is confirmed that the roughness is less than or equal to 1.0 nmRz in Example 6, so the polishing pad can completely follow the shape of the workpiece. Compared with Example 5, each cell has a flattened shape, so the cells in each layer are not connected to each other, which leads to increased followability and reduced roughness.
[0098] In Example 7, the precursor was prepared according to the same procedure as in Example 5. In Example 7, Matsumoto Microsphere FN-78D (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) was added to the polishing layer precursor as a third hollow particle. In order to perform the compression process, 25.06 g of the sealing layer precursor was placed in the mold and temporarily cured, and then 87.20 g of the polishing layer precursor (increased in amount) was placed on the sealing layer precursor. After that, a discharge hole with a diameter of φ3 mm formed in the side surface of the mold was opened, and a top cover was covered on the upper surface of the mold. While the precursor was heated for formal curing, the top cover was moved to compress the inside of the mold until the thickness became 50% of the initial thickness before compression. This state was maintained until the resin no longer flowed. Excess resin was discharged from the discharge hole.
[0099] In the polishing pad according to Example 7, the thickness of the sealing layer is 0.47 mm, and the thickness of the polishing layer is 1.09 mm. The maximum thickness of each cell in the sealing layer in the stacking direction is 0.30 mm, the thickness of each cell in the polishing layer in the stacking direction is 0.74 mm, and the average cell diameter in the polishing surface is 300 μm. The maximum cell diameter is 2.1 mm, and each cell has a flattened shape in the stacking direction. The water contact angle of the support surface is 120.6°, and the cell density in the sealing layer is 60%. The water contact angle of the polishing surface is 49.5°, and the cell density in the polishing layer is 62%. The water vapor permeability is 8.4 g / m 2 ·24h.
[0100] As can be seen from Table 1, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 7, so the polishing pad could completely follow the shape of the workpiece. Although the thickness of each cell was smaller than that in Example 6, it was confirmed that the thickness of each cell had little effect on the maximum roughness.
[0101] In Example 8, the precursor was prepared according to the same procedure as in Example 5. In Example 6, Matsumoto Microsphere F-65DE (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) was added to the polishing layer precursor as a third hollow particle. In order to perform the compression process, 18.98 g of the sealing layer precursor was placed in the mold and temporarily cured, and then 66.06 g of the polishing layer precursor (increased in amount) was placed on the sealing layer precursor. After that, a discharge hole with a diameter of φ3 mm formed in the side surface of the mold was opened, and a top cover was covered on the upper surface of the mold. While the precursor was heated for formal curing, the top cover was moved to compress the inside of the mold until the thickness became 66% of the initial thickness before compression. This state was maintained until the resin no longer flowed. Excess resin was discharged from the discharge hole.
[0102] In the polishing pad according to Example 5, the thickness of the sealing layer is 0.47 mm, and the thickness of the polishing layer is 1.09 mm. The maximum thickness of each cell in the sealing layer in the stacking direction is 0.42 mm, the thickness of each cell in the polishing layer in the stacking direction is 0.98 mm, and the average cell diameter in the polishing surface is 50 μm. The maximum cell diameter is 1.8 mm, and each cell has a flattened shape in the stacking direction. The water contact angle of the support surface is 120.6°, and the cell density in the sealing layer is 60%. The water contact angle of the polishing surface is 49.5°, and the cell density in the polishing layer is 62%. The water vapor permeability is 9.2 g / m 2 ·24h.
[0103] As can be seen from Table 1, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 5, so the polishing pad could completely follow the shape of the workpiece. Although the average cell diameter was smaller than that in Example 6, the average cell diameter had little effect on the maximum roughness.
[0104] In Example 9, the amount of polytetrafluoroethylene particles was increased to 8.15 g to increase the water contact angle of the sealing layer. A polishing pad according to Example 6 was prepared in the same manner as in Example 1 in the subsequent processes from degassing to curing.
[0105] In the polishing pad according to Example 9, the thickness of the sealing layer is 0.51 mm, and the thickness of the polishing layer is 0.86 mm. The water contact angle of the supporting surface is 150.6°, and the cell density in the sealing layer is 59%. The water contact angle of the polishing surface is 71.8°, and the cell density in the polishing layer is 60%. The water vapor permeability is 9.2 g / m 2 ·24h.
[0106] As can be seen from Table 1, it is confirmed that the roughness is less than or equal to 1.0 nmRz in Example 9, so the polishing pad can completely follow the shape of the workpiece. Although the water contact angle of the sealing layer is greater than that in Example 1, it is confirmed that the water contact angle of the sealing layer has little effect on the maximum roughness.
[0107] In Comparative Example 1, a precursor was prepared in the same procedure as in Example 3. Thereafter, 12.53 g of the sealing layer precursor was first placed in a mold and cured in an oven at 120° C. for 4 hours. Thereafter, the cured sealing layer precursor was demolded from the mold. Next, 43.60 g of the polishing layer precursor was placed in the mold, once cured at 120° C. for 4 hours, and then the cured polishing layer precursor was demolded from the mold. Then, the sealing layer precursor and the polishing layer precursor were bonded together with 1.1 g of an adhesive (Cemedine Super X). Thus, a polishing pad according to Comparative Example 1 was prepared.
[0108] In the polishing pad according to Comparative Example 1, the thickness of the sealing layer was 0.47 mm, the thickness of the polishing layer was 0.95 mm, and the thickness of the adhesive was 0.09 mm. The water contact angle of the supporting surface was 120.8°, and the cell density in the sealing layer was 60%. The water contact angle of the polishing surface was 15.1°, and the cell density in the polishing layer was 62%. The water vapor permeability was 15.1 g / m 2 ·24h.
[0109] The roughness was evaluated in the same manner as in Example 1. As can be seen from Table 1, the roughness in Comparative Example 1 was greater than 1.0 nmRz. This result indicates that the gap formed during bonding leads to uneven bonding. When air, polishing solution, etc. enter the gap, it causes a distribution of fluid pressure. This causes the polishing pad to deteriorate in its ability to follow the shape of the object to be polished, which makes it difficult to obtain high surface accuracy.
[0110] In Comparative Example 2, a polishing pad was prepared in the same procedure as in Example 1. In this case, polytetrafluoroethylene particles were not incorporated into the sealing layer precursor. In the subsequent procedures from degassing to curing, a polishing pad was prepared in the same manner as in Example 1.
[0111] In the polishing pad according to Comparative Example 2, the thickness of the sealing layer was 0.38 mm, and the thickness of the polishing layer was 0.95 mm. The water contact angle of the supporting surface was 71.1°, and the cell density in the sealing layer was 62%. The water contact angle of the polishing surface was 72.3°, and the cell density in the polishing layer was 60%. The water vapor permeability was 300 g / m 2 ·24h.
[0112] The roughness was evaluated in the same manner as in Example 1. As can be seen from Table 1, it was confirmed that the roughness in Comparative Example 2 was greater than 1.0 nmRz. This result indicates that since the water contact angle of the support surface was less than 90°, liquid flowed out of the pores, making it difficult to obtain high surface accuracy.
[0113] In Comparative Example 3, a polishing pad was prepared according to the same procedure as in Example 5. However, a polishing layer was not prepared, and only a sealing layer was formed, thereby preparing a polishing pad according to Comparative Example 3.
[0114] In the polishing pad of Comparative Example 3, the thickness of the sealing layer is 0.94 mm. The water contact angle of the support surface is 122.0°, and the cell density in the sealing layer is 60%. The water vapor permeability is 10.9 g / m 2 ·24h.
[0115] The roughness was evaluated in the same manner as in Example 1. As can be seen from Table 1, the roughness in Comparative Example 3 was greater than 1.0 nmRz. This result shows that since there is no hydrophilic surface such as the polishing surface, the polishing solution cannot be sufficiently retained, which makes it difficult to obtain high surface accuracy.
[0116] Table 1
[0117]
[0118] As can be seen from the above results, it is confirmed that in the polishing pad according to the present disclosure formed by a resin molded body (the resin molded body has a structure in which a polishing layer and a sealing layer are stacked in sequence, the polishing layer includes a polishing surface, the water contact angle of the polishing surface is smaller than the water contact angle of the supporting surface, and the sealing layer includes the supporting surface with a water contact angle of 90° or more), even when the polishing pad is used for fluid-supported processing and fluid pressure is applied, the fluid does not easily reach the polishing surface. It is also confirmed that since the polishing pad is formed by the resin molded body and does not include any adhesive layer made of an adhesive, it is possible to maintain high followability to the shape or warping of the workpiece. Therefore, in the polishing pad according to the present disclosure, the surface roughness of the workpiece can be sufficiently reduced compared with the polishing pad for fluid-supported polishing according to the prior art.
[0119] [Polishing pad]
[0120] Figure 5A and Figure 5B is a schematic diagram of a polishing pad 10 according to the present disclosure. Figure 5A is a perspective view of the polishing pad 10, Figure 5B is along Figure 5A FIG. 1 is a cross-sectional view of the polishing pad 10 taken along line AA in the z-axis direction.
[0121] exist Figure 5A and Figure 5B In FIG. 1 , a plane parallel to the polishing surface 11S is defined as an xy plane, and an axis perpendicular to the xy plane is defined as a z axis. Figure 5A The line AA shown by the middle dashed line is parallel to the x-axis and perpendicular to the y-axis. The polishing pad 10 has a structure in which the first region 12, the second region 13, and the sealing layer 14 are sequentially positioned from the polishing surface 11S in the negative z direction. The polishing pad 10 according to the present disclosure includes a hard first region 12 having high hardness, a soft second region having low hardness to follow the warpage of the workpiece 3, and a sealing layer 14 for sealing fluid pressure, which are sequentially formed from the polishing surface 11S to reduce the roughness to be removed by the polishing process.
[0122] The polishing surface 11S is a portion of the polishing pad 10 that contacts the workpiece 3. The first cells 8A are preferably located in the polishing surface 11S. The first cells 8A located in the polishing surface 11S enable the polishing surface 11S to hold the slurry S on its surface. If the polishing surface 11S can hold the slurry S, the slurry S can be supplied to the space between the polishing pad 10 and the workpiece 3 even when the polishing pad 10 and the workpiece 3 are in contact with each other during the polishing process.
[0123] The first region 12 includes a resin 7 and first cells 8A, and has a first hardness. The front side of the first region 12 corresponds to the polishing surface 11S, and is used to prevent the polishing pad 10 from following the shape of a portion of the workpiece 3 to be removed by polishing (e.g., a corrugated portion with a high spatial frequency). The desired first hardness can be obtained by controlling the amount of the first cells 8A (average cell density). If the content of the first hollow particles (whose hollow portion can be used as the first cells 8A) increases, the first hardness can be reduced; if the content of the first hollow particles decreases, the first hardness can be increased. However, if the first hardness is too high, the deformation to follow the shape of the workpiece 3 will be insufficient. In order to increase the degree of freedom of deformation of the workpiece 3 or prevent the polishing pad 10 from excessively following the shape of the workpiece 3, the average cell density in the first region 12 is preferably in the range of 10% to 40%. The method for measuring the average cell density will be described later. From the same point of view, the value of the first hardness is preferably in the range of 0.016GPa to 0.06GPa. The method for measuring the hardness will be described later.
[0124] The second region 13 includes the resin 7 and the second cells 8B, and has a second hardness lower than the first hardness. The second region 13 having a second hardness lower than the first hardness helps the polishing pad 10 to follow the shape of the workpiece 3. The desired second hardness can be obtained by controlling the amount (average cell density) of the second cells 8B. If the content of the second hollow particles (whose hollow part can be used as the second cells 8B) increases, the second hardness can be reduced; if the content of the second hollow particles decreases, the second hardness can be increased. In order to set the second hardness lower than the first hardness, the average cell density in the second region 13 is preferably higher than the average cell density in the first region 12. In addition, since the average equivalent circular diameter of the second cells 8B is preferably larger than the average equivalent circular diameter of the first cells 8A, the average particle size of the second hollow particles is preferably larger than the average particle size of the first hollow particles. Similarly, the linear expansion coefficient of the second hollow particles is preferably larger than the linear expansion coefficient of the first hollow particles. The second hardness is lower than the first hardness. The greater the difference between the second hardness and the first hardness, the easier it is for the polishing pad 10 to follow the shape of the workpiece 3. However, if the second hardness is too low, the reproducibility of polishing deteriorates or the possibility of damage to the workpiece 3 increases depending on the material of the workpiece 3. Therefore, from the viewpoint of improving the followability of the polishing pad 10 to the shape of the workpiece 3 and ensuring the reproducibility of the polishing process, the average cell density value in the second region 13 is preferably in the range of 40% to 80%. From the same viewpoint, the value of the second hardness is preferably greater than or equal to 0.003 GPa and less than 0.016 GPa. In order to follow the warpage of the workpiece 3, etc., the thickness of the second region 13 ( Figure 5B The length in the z direction of the second region 13 is preferably greater than the thickness of the first region 12 and the thickness of the sealing layer 14. More preferably, the thickness of the second region 13 is more than 1.5 times the thickness of the first region 12. More preferably, the thickness of the second region 13 is more than twice the thickness of the first region 12.
[0125] The sealing layer 14 includes the resin 7 and the supporting surface of the polishing pad. The average cell density in the sealing layer 14 is lower than the average cell density in the first region 12 and the second region 13. The value of the average cell density in the sealing layer 14 is not particularly limited, but is preferably 10% or less. If the average cell density in the sealing layer 14 is too high, the cells are more likely to be connected to each other. In this case, the fluid supplied from the fluid storage portion 6 is likely to reach the workpiece 3 via the sealing layer 14, the second region 13, the first region 12 and the polishing surface 11S. The hardness of the sealing layer 14 is preferably higher than the first hardness and the second hardness. The thickness of the sealing layer 14 ( Figure 5B The length in the z-direction) is preferably smaller than the thickness of the first region 12 and the thickness of the second region 13.
[0126] The polishing pad 10 is a resin molded body. Specifically, the polishing surface 11S, the first region 12, the second region 13 and the sealing layer 14 are integrally formed without using an adhesive. The raw material of the resin material used as the curing material for forming the resin molded body is not particularly limited. For example, polyurethane, polyethylene, polypropylene, polystyrene, polyester, nylon, polyvinyl chloride, polyvinylidene chloride, polybutene, polyacetal, polyphenylene ether, polyvinyl alcohol, polymethyl methacrylate, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyamideimide, polycarbonate, polyarylate, liquid crystal polymer, aromatic polysulfone resin, biodegradable polyester resin, polyamide resin, polyimide resin, fluororesin, ethylene-propylene resin, ethylene-ethyl acrylate resin, epoxy resin, acrylic resin, norbornene-based resin, styrene copolymer (e.g., vinyl polyisoprene-styrene copolymer, butadiene-styrene copolymer, acrylonitrile-styrene copolymer or acrylonitrile-butadiene-styrene copolymer), natural rubber, synthetic rubber or thermoplastic elastomer can be used. Examples of these resin materials may be used alone, or may be mixed or copolymerized. From the viewpoint of excellent wear resistance and from the viewpoint of convenience of the manufacturing process described below, it is preferred to use polyurethane as the main component. The term "main component of a resin molded body" as used herein refers to the component with the largest mass among the resin materials contained in the resin molded body when the resin molded body is formed from a plurality of resin materials. The proportion of polyurethane in the resin molded body is greater than or equal to 50% by mass, preferably greater than or equal to 70% by mass, and more preferably greater than or equal to 90% by mass. The method for manufacturing the resin molded body will be described later.
[0127] The air permeability of the polishing pad 10 is preferably 50 ml / m 2 ·24hr·atm or less. If the air permeability is less than or equal to this value, the polishing pad 10 easily follows the shape of the workpiece 3 even when the fluid is supplied from the fluid storage section 6 to the polishing pad 10. On the other hand, if the air permeability is greater than this value, the fluid pressure applied to the polishing pad 10 is too large, which makes it difficult for the polishing pad 10 to follow the shape of the workpiece 3. If it is difficult for the polishing pad 10 to follow the shape of the workpiece 3, the polishing process cannot be fully performed, which makes it difficult to reduce the surface roughness of the workpiece 3.
[0128] The thickness of the polishing pad 10 ( Figure 5B The length in the z direction is preferably in the range of 0.3 mm to 2.0 mm. This is because if the thickness is within this range, the polishing pad 10 can easily follow the shape or warping of the workpiece 3.
[0129] As described above, the polishing pad 10 according to the present disclosure is formed of a resin molded body having the following structure, wherein a polishing surface, a first region having a first hardness, a third region having a second hardness lower than the first hardness, and a sealing layer are stacked in sequence. Therefore, even when the polishing pad is used for fluid-supported polishing and fluid pressure is applied, the fluid does not easily reach the polishing surface. In addition, since the polishing pad 10 is formed of a resin molded body that does not include any adhesive layer made of an adhesive, high followability to the shape or warping of the workpiece 3 can be maintained. Therefore, compared with the polishing pad for fluid-supported polishing of the prior art, the polishing pad 10 according to the present disclosure can substantially reduce the roughness on the surface of the workpiece.
[0130] Although the present disclosure describes an example in which the first cells 8A are smaller than the second cells 8B, any other form may be used as long as the second hardness of the second region 13 is lower than the first hardness of the first region 12. Any other member may be provided on the lower surface of the sealing layer 14 as long as the polishing pad 10 is formed of a resin molded body.
[0131] [Manufacturing method of polishing pad]
[0132] Next, a method for manufacturing the polishing pad 10 will be described. The method for manufacturing the polishing pad 10 according to the present disclosure is not particularly limited. Figure 6 and FIG. 7A to FIG. 7D Describe the preferred method.
[0133] First, in step S11, Fig. 7A As shown, the first region precursor is placed in the mold 20 and then heated to temporarily cure it. The first region precursor 12A is a mixture of a thermoplastic resin, a curing agent and first hollow particles. The first region precursor 12A becomes the first region 12 of the polishing pad 10 after formal curing. The front of the first region 12 corresponds to the polishing surface 11S. There is no particular limitation on the size and type of the mold 20. The desired size of the mold 20 can be set according to the shape of the polishing pad 10 to be manufactured. The mold 20 is, for example, a mold. In the case of mixing the thermoplastic resin, the curing agent and the first hollow particles, it is preferred to use a degasser or the like to remove bubbles. The temporary curing temperature may be less than or equal to the formal curing temperature described below, and may be appropriately set according to the material of the thermoplastic resin used. If the temporary curing temperature is equal to the formal curing temperature, the temporary curing time is preferably shorter than the formal curing time.
[0134] Next, in step S12, Figure 7BAs shown, the second region precursor is placed on the first region precursor 12A that has been temporarily cured in the mold 20, and then the second region precursor is heated to temporarily cure it. The second region precursor 13A is a mixture of a thermoplastic resin, a curing agent and a second hollow particle. The second region precursor 13A becomes the second region 13 of the polishing pad 10 after formal curing. In the case of mixing a thermoplastic resin, a curing agent and a second hollow particle, it is preferred to use a degasser or the like to remove bubbles. The temporary curing temperature is preferably lower than the formal curing temperature described below, and can be appropriately set according to the material of the thermoplastic resin used. The content and / or particle size of the second hollow particles are selected so that the second hardness of the second region 13 is lower than the first hardness of the first region 12. The average particle size of the second hollow particles is preferably greater than the average particle size of the first hollow particles. The linear expansion coefficient of the second hollow particles is preferably greater than the linear expansion coefficient of the first hollow particles.
[0135] Next, in step S13, Figure 7C As shown, the sealing layer precursor is placed on the second region precursor that has been temporarily cured in the mold 20, and then the sealing layer precursor is heated for temporary curing. The sealing layer precursor 14A is a mixture of a thermoplastic resin and a curing agent. The sealing layer precursor 14A becomes the sealing layer 14 of the polishing pad 10 after formal curing. In order to reduce the cell density in the sealing layer 14, the sealing layer precursor 14A preferably does not contain hollow particles. In the case of mixing the thermoplastic resin and the curing agent, it is preferred to use a degasser or the like to remove bubbles. The temporary curing temperature may be less than or equal to the formal curing temperature described below, and may be appropriately set according to the material of the thermoplastic resin to be used. If the temporary curing temperature is equal to the formal curing temperature, the temporary curing time is preferably shorter than the formal curing time.
[0136] In step S14, Fig.7D As shown, the first region precursor 12A, the second region precursor 13A and the sealing layer precursor 14A are heated to perform formal curing. The formal curing temperature may be greater than or equal to the above-mentioned temporary curing temperature, and may be appropriately set according to the material of the thermoplastic resin to be used. If the temporary curing temperature is equal to the formal curing temperature, the formal curing time is preferably longer than the temporary curing time. The formal curing process may be performed after the temporary curing precursor of the polishing pad 10 is demolded from the mold 20 after step S13.
[0137] Through the above steps, the polishing pad 10 according to the present disclosure can be manufactured.
[0138] The above-mentioned method for manufacturing the polishing pad 10 according to the present disclosure does not include any process of bonding the regions together with an adhesive, and the regions are integrally formed, thereby being able to provide a polishing pad that can maintain a high degree of followability to the shape or warpage of the workpiece 3. Therefore, compared with the polishing pad for fluid-supported polishing according to the prior art, the method for manufacturing the polishing pad 10 according to the present disclosure can provide a polishing pad that can sufficiently reduce the surface roughness of the workpiece.
[0139] In the above-mentioned manufacturing method, temporary curing and formal curing are performed by placing the first region precursor 12A, the second region precursor 13A and the sealing layer precursor 14A in the mold 20 in sequence. Alternatively, temporary curing and formal curing can be performed by placing the sealing layer precursor 14A, the second region precursor 13A and the first region precursor 12A in the mold 20 in sequence. In addition, in the above-mentioned manufacturing method, the hardness of the first region 12 and the hardness of the second region 13 are adjusted by changing the size or content of the hollow particles. However, the manufacturing method is not limited to this method. For example, the hardness of each layer can be controlled by intentionally foaming the precursor in each layer when mixing the first region precursor 12A and the second region precursor 13A.
[0140] The present disclosure will be described in more detail below with reference to examples. However, the present disclosure is not limited to the following examples.
[0141] Prior to describing the examples to be manufactured, a method for evaluating each example and each comparative example will be described.
[0142] [Polishing pad evaluation method]
[0143] (Indentation hardness)
[0144] Measuring instrument: Nanoindenter G200 manufactured by TOYO Corporation
[0145] Test method: A sample (φ70 mm) was cut from the polishing pad according to the thickness to be evaluated, placed on the sample table, and 12 locations on each sample were measured by using a Berkovich indenter and setting the indentation depth to 10 μm in XR mode, and the average value was calculated.
[0146] (Breathability)
[0147] Measuring instrument: air permeability tester
[0148] Test method: By differential gas chromatography (pressure difference method) in accordance with JIS K 7126-1, test nitrogen is allowed to flow to one side of the sample membrane (φ70 mm) at atmospheric pressure and the other side of the membrane, i.e., the permeate side, is depressurized. Each sample is measured three times and the average value is calculated.
[0149] (Average cell density)
[0150] Measuring instrument: Color 3D laser microscope (VK-9700 manufactured by Keyence Corporation)
[0151] Test method: The average cell density is calculated by measuring a cross section of a sample (10 mm×10 mm) with a 10x objective lens, converting the resin portion and the cell portion into grayscale by image processing, and binarizing the obtained information at 125 grayscales.
[0152] (thickness)
[0153] Measuring instrument: Color 3D laser microscope (VK-9700 manufactured by Keyence Corporation)
[0154] Test method: The thickness of each layer was measured by measuring the cross section of the sample (10 mm×10 mm) with a 10x objective lens.
[0155] (Workpiece roughness)
[0156] Measuring instrument: White interferometer (CP300 manufactured by Zygo, Inc.)
[0157] Test method: Use a 5x objective lens to measure the area 35mm to the right and 35mm to the left of the center of the test workpiece (φ80mm) and evaluate the roughness Rz (JIS B 0601-2001) of the entire measurement area. The resolution is 0.01nm.
[0158] (Follow-up)
[0159] Test method: A workpiece of a glass substrate with a surface roughness of 50 nmRz and a diameter of φ80 mm was used, and polishing was performed for 30 minutes by adding cerium oxide (K30-9 manufactured by Mirek Corporation) as a slurry, and the maximum roughness Rz was evaluated. In this case, the maximum roughness of 1 nmRz was set as the judgment value to determine whether the polishing pad can follow the shape of the workpiece. This is because: if the polishing pad cannot follow the shape of the workpiece and cannot perform polishing uniformly, an unprocessed portion will remain and a roughness less than or equal to the judgment value cannot be obtained. The result indicating that the roughness is less than or equal to 1 nmRz is evaluated as "A", and the result indicating that the roughness is greater than 1 nmRz is evaluated as "B".
[0160] [Manufacture of polishing pad]
[0161] As a resin material, polyurethane elastomer Coronate 4370 (manufactured by TOSOH CORPORATION), i.e., a thermoplastic resin, was prepared, and as a curing agent, polyol-based curing agent Nipporan 4479 (manufactured by TOSOH CORPORATION) was prepared. As first hollow particles, Matsumoto Microsphere F-80DE (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) was prepared, and as second hollow particles, Matsumoto Microsphere FN-78D (manufactured by Matsusoto Yushi Pharmaceutical Co., Ltd.) having a larger linear expansion coefficient and particle size than the first hollow particles was prepared.
[0162] The first region precursor is obtained by mixing a resin material, a curing agent and first hollow particles and removing bubbles by a degasser. The second region precursor is obtained by mixing a resin material, a curing agent and second hollow particles and removing bubbles by a degasser. The sealing layer precursor is obtained by mixing a resin material and a curing agent and removing bubbles by a degasser.
[0163] The first region precursor was placed in a square mold with a bottom surface of 200×200 mm and temporarily cured at 120° C. for 10 minutes in an electric furnace. Next, the second region precursor was placed on the temporarily cured first region precursor and temporarily cured at 120° C. for 10 minutes in an electric furnace. After that, the sealing layer precursor was placed on the temporarily cured second region precursor and once cured at 120° C. for 2 hours in an electric furnace. After that, the temporarily cured polishing pad precursor was demolded from the mold. Then, the polishing pad precursor was secondary cured at a temperature condition of 120° C. for 8 hours. Thus, a polishing pad according to Example 1 was obtained.
[0164] In the polishing pad according to Example 1, the thickness of the polishing pad is 1.5 mm, the thickness of the first region is 0.4 mm, the thickness of the second region is 0.8 mm, and the thickness of the sealing layer is 0.3 mm. Table 2 shows a list of evaluation results of indentation hardness, air permeability, cell density, workpiece roughness, and followability. As can be seen from Table 2, it is confirmed that in Example 1, the roughness is less than or equal to 1 nmRz, so the polishing pad can completely follow the shape of the workpiece.
[0165] The polishing pad according to Example 2 was obtained in the same procedure as Example 1, except that the second hollow particle content in Example 2 was less than that in Example 1. As can be seen from Table 2, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 2 and thus the polishing pad could completely follow the shape of the workpiece. It was also confirmed that the hardness of the second region in Example 2 was higher than that in Example 1, and thus the roughness increased.
[0166] The polishing pad according to Example 3 was obtained in the same procedure as Example 1, except that the first hollow particle content in Example 3 was greater than that in Example 1 and the second hollow particle content in Example 3 was less than that in Example 1. As can be seen from Table 2, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 3, so the polishing pad could completely follow the shape of the workpiece. It was also confirmed that the hardness of the first region in Example 3 was lower than that in Example 1, and the hardness of the second region in Example 3 was higher than that in Example 1, so the roughness increased.
[0167] The polishing pad according to Example 4 was obtained in the same procedure as Example 3, except that the first hollow particle content in Example 4 was less than that in Example 3. As can be seen from Table 2, it was confirmed that the roughness was less than or equal to 1.0 nmRz in Example 4, and thus the polishing pad could completely follow the shape of the workpiece. It was also confirmed that the hardness of the first region in Example 4 was higher than that in Example 3, and thus the roughness was reduced.
[0168] In Comparative Example 1, polyurethane elastomer Coronate 4370 (manufactured by TOSOH CORPORATION), i.e., thermoplastic resin, was prepared as a resin material, and Nipporan 4479 (manufactured by TOSOH CORPORATION) was prepared as a curing agent. Matsumoto Microsphere F-80DE (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd.) was prepared as a first hollow particle, and Matsumoto Microsphere FN-78D (manufactured by Matsusoto Yushi Pharmaceutical Co., Ltd.) having a larger linear expansion coefficient and particle size than the first hollow particle was prepared as a second hollow particle.
[0169] The first molded body precursor is obtained by mixing a resin material, a curing agent and first hollow particles and removing bubbles by a degasser. The second molded body precursor is obtained by mixing a resin material, a curing agent and second hollow particles and removing bubbles by a degasser. The sealing layer precursor is obtained by mixing a resin material and a curing agent and removing bubbles by a degasser.
[0170] The first molded body was obtained by placing the first molded body precursor in a square mold having a bottom surface of 200×200 mm and curing the first molded body precursor in an electric furnace at 120° C. for 10 minutes. The thickness of the first molded body was 0.4 mm.
[0171] The second molded body was obtained by placing the second molded body precursor in a square mold having a bottom surface of 200×200 mm and curing the second molded body precursor in an electric furnace at 120° C. for 10 minutes. The thickness of the second molded body was 0.8 mm.
[0172] Thereafter, the first molded body and the second molded body were bonded together with an adhesive (Cemedine 575F) to obtain a bonded body. Thereafter, a rubber sheet made of nitrile and having a thickness of 0.3 mm was bonded to the second molded body side of the bonded body with an adhesive. In this bonding process, a spatula was used for each of the first molded body and the second molded body, and the polishing pad according to Comparative Example 1 was obtained by bonding the first molded body and the second molded body while uniformly spreading the first molded body and the second molded body.
[0173] The roughness was evaluated in the same manner as in Example 1. As can be seen from Table 2, the roughness in Comparative Example 1 was greater than 1.0 nmRz. This is because uneven bonding occurred during the bonding process between the polishing pad and the rubber sheet, which made it difficult for the polishing pad to follow the shape of the workpiece and perform polishing uniformly.
[0174] Comparative Example 2 is different from Example 3 in that the sealing layer precursor is not placed in the mold, and the thickness of the second region in Comparative Example 2 is different from the thickness of the second region in Example 3. Except for the above differences, the polishing pad according to Comparative Example 2 is obtained by the same process as Example 3. The thickness of the polishing pad is 1.5 mm, the thickness of the first region is 0.4 mm, and the thickness of the second region is 1.1 mm. As shown in Table 2, it is confirmed that the roughness in Comparative Example 2 is greater than 1.0 nmRz. Due to the high air permeability, the fluid pressure becomes greater than or equal to the threshold value, which makes it difficult for the polishing pad to follow the shape of the workpiece and to fully perform the polishing process, resulting in an increase in roughness.
[0175] Table 2
[0176]
[0177] As can be seen from the above results, it is confirmed that in the polishing pad according to the present disclosure formed by a resin molded body having a structure in which a polishing surface, a first region having a first hardness, a second region having a second hardness lower than the first hardness, and a sealing layer are sequentially stacked, the fluid is not easy to reach the polishing surface even when the polishing pad is used for fluid-supported processing and fluid pressure is applied. It is also confirmed that since the polishing pad is formed of a resin molded body and does not include any adhesive layer made of an adhesive, high followability to the shape or warping of the workpiece can be maintained. Therefore, in the polishing pad according to the present disclosure, the surface roughness of the workpiece can be sufficiently reduced compared with the polishing pad for fluid-supported polishing according to the prior art.
[0178] The present disclosure is not limited to the above exemplary embodiments, but can be modified in various ways within the technical concept of the present disclosure. The advantageous effects described in the exemplary embodiments are merely examples of the expected advantageous effects produced by the present disclosure, and the advantageous effects of the present disclosure are not limited to those described in the exemplary embodiments.
[0179] Although the exemplary embodiments of the present disclosure have been described with reference to the exemplary embodiments, it should be understood that the present disclosure is not limited to the disclosed exemplary embodiments. The scope of the following claims is to be accorded the broadest interpretation so as to encompass all modifications and equivalent structures and functions.
Claims
1. A polishing pad comprising: a polishing layer comprising a polishing surface; and a sealing layer comprising a support surface, Among them, the polishing layer and the sealing layer are arranged in sequence. The polishing surface is set as the front side, and the supporting surface is set as the back side. Wherein, the support surface has a water contact angle of more than 90°, wherein the water contact angle of the polishing surface is smaller than the water contact angle of the supporting surface, and Here, the polishing pad is formed of a resin molded body.
2. The polishing pad according to claim 1, wherein The water contact angle of the support surface is 150° or less.
3. The polishing pad according to claim 1, wherein The sealing layer includes fluororesin particles.
4. The polishing pad according to claim 3, wherein: The content of the fluororesin particles in the sealing layer is in the range of 20% by mass to 50% by mass.
5. The polishing pad according to claim 3, wherein: The fluororesin particles include polytetrafluoroethylene.
6. The polishing pad according to claim 1, wherein The polishing layer comprises hydrophilic metal oxide particles.
7. The polishing pad according to claim 6, wherein: The metal oxide particles include at least one of silicon dioxide and aluminum oxide.
8. The polishing pad according to claim 6, wherein: The content of the metal oxide particles in the polishing layer is in the range of 20% by mass to 50% by mass.
9. The polishing pad according to claim 1, wherein: The resin molded body includes a foamed body, the foamed body includes cells, each of the cells being in a collapsed shape in a thickness direction of the polishing pad.
10. The polishing pad according to claim 9, wherein: The length of the collapsed shape of each cell in the polishing layer and the sealing layer in the thickness direction is less than or equal to the thickness of the polishing layer and the thickness of the sealing layer.
11. The polishing pad according to claim 9, wherein: The average cell diameter of the cells in the polished surface is in the range of 50 μm to 300 μm.
12. The polishing pad according to claim 1, wherein The water vapor permeability of the polishing pad is 25g / m 2 Less than 24 hours.
13. The polishing pad according to claim 1, wherein: The polishing pad contains polyurethane as a main component.
14. The polishing pad according to claim 1, wherein: The thickness of the polishing pad is in the range of 0.3 mm to 2.0 mm.
15. A polishing device configured to polish a workpiece placed on a polishing surface of a polishing pad, the polishing device comprising: Pedestal; a polishing pad fixed to a base; and a fluid storage portion configured to store a fluid for applying pressure to the polishing pad from the sealing layer side, Among them, the polishing pad includes: a polishing layer comprising a polishing surface; and a sealing layer comprising a support surface, Among them, the polishing layer and the sealing layer are arranged in sequence. The polishing surface is set as the front side, and the supporting surface is set as the back side. Wherein, the support surface has a water contact angle of more than 90°, wherein the water contact angle of the polishing surface is smaller than the water contact angle of the supporting surface, and Here, the polishing pad is formed of a resin molded body.
16. A polishing pad comprising: Polished surface; First region; Second area; and Sealing layer, The polishing surface, the first region, the second region and the sealing layer are arranged in sequence. wherein the first region includes first cells and has a first hardness, wherein the second region includes second cells and has a second hardness lower than the first hardness, wherein the average cell density in the sealing layer is lower than the average cell density in the first region and the second region, and Here, the polishing pad is formed of a resin molded body.
17. The polishing pad according to claim 16, wherein: The air permeability of the polishing pad is 50ml / m 2 ·24hr·atm or less.
18. The polishing pad according to claim 16, wherein: The average cell density in the second region is higher than the average cell density in the first region.
19. The polishing pad according to claim 18, in, The average cell density in the first region is in the range of 10% to 40%, and Wherein, the average cell density in the second region is in the range of 40% to 80%.
20. The polishing pad according to claim 16, wherein The average equivalent circular diameter of the second cells is greater than the average equivalent circular diameter of the first cells.
21. The polishing pad according to claim 16, wherein The average cell density in the sealing layer is 10% or less.
22. The polishing pad according to claim 16, wherein: The hardness of the sealing layer is higher than the first hardness and the second hardness.
23. The polishing pad according to claim 16, wherein: The polishing pad contains polyurethane as a main component.
24. The polishing pad according to claim 16, wherein: The thickness of the polishing pad in a direction in which the polishing surface, the first region, the second region, and the sealing layer are sequentially arranged is in a range of 0.3 mm to 2.0 mm.
25. The polishing pad according to claim 16, wherein: The thickness of the second region is greater than the thickness of the first region and the thickness of the sealing layer.
Citation Information
Patent Citations
Abrasive pad and manufacturing method for the same
JP2003220550A
Polishing tool and polishing method
JP2004358591A
Multi-layer polishing pad material for cmp
CN101184582A
Adsorption pad for fine grinding
CN106985061A
Polishing pad comprising hydrophobic region and endpoint detection port
CN1933939A